Mechanistic Insights and Optimization of Phytol Recovery from Acacia Auriculiformis Leaves Using Zinc Chloride Catalysis - Ali, Abubakar; Ibrahim, Haruna (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
This study explores a sustainable and environmentally friendly approach for phytol production from Acacia auriculiformis leaves, an underutilized lignocellulosic biomass, in response to the growing global demand for renewable bio-based chemicals. The research aims to optimize phytol extraction through zinc chloride–catalyzed thermal hydrolysis under mild reaction conditions while maintaining high selectivity and yield. The method employs ZnCl₂ as a Lewis acid catalyst to facilitate chlorophyll cleavage, with systematic variation of reaction temperature (40–80 °C) and catalyst loading (0.5–1.5% w/w) to determine optimal processing conditions. The highest phytol yield, 646.26 mg/g (13.14%), was obtained at 50 °C with 0.5% ZnCl₂, exceeding yields reported for other plant sources and conventional extraction techniques. Product characterization using gas chromatography–mass spectrometry (GC-MS) confirmed phytol as the dominant compound, accompanied by minor hydrolysis by-products. Mechanistic analysis revealed that yield variations were influenced by the balance between phytol formation and thermal degradation pathways under different catalytic and temperature conditions. These findings demonstrate the strong potential of A. auriculiformis leaves as a renewable feedstock for phytol production and highlight the effectiveness of ZnCl₂-assisted hydrolysis in supporting circular bio-economy and green chemistry principles. However, further studies are recommended to evaluate process scalability, economic feasibility, and environmental impacts to support industrial-level application.